2022
DOI: 10.1093/cdn/nzac075
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Feeding Social and Behavior Change Communication for Fathers and Mothers Improves Children’s Consumption of Fish and Eggs and Minimum Meal Frequency in Kaduna State, Nigeria

Abstract: Background Fathers are key influencers of complementary feeding practices, but few studies in low- and middle-income countries have measured the effects of complementary feeding social and behavior change communication (SBCC) targeted at both fathers and mothers. Objective To measure the effects of an SBCC intervention on children's dietary diversity (primary outcome) and other complementary feeding indicators, fathers’ and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
0
10
1
Order By: Relevance
“…The radio and TV ads were aired 7–8 times per day. Findings from the evaluation of the intervention, which have been documented elsewhere ( 25 ), show low reported exposure to the intervention components, with fathers’ reported exposure ranging from 11% to 26% and mothers’ reported exposure ranging from 12% to 21%. Mothers who reported exposure to intervention messages through CBOs, religious services, home visits, and on TV had increased odds of feeding their children eggs and fish the previous day.…”
Section: Methodsmentioning
confidence: 72%
See 1 more Smart Citation
“…The radio and TV ads were aired 7–8 times per day. Findings from the evaluation of the intervention, which have been documented elsewhere ( 25 ), show low reported exposure to the intervention components, with fathers’ reported exposure ranging from 11% to 26% and mothers’ reported exposure ranging from 12% to 21%. Mothers who reported exposure to intervention messages through CBOs, religious services, home visits, and on TV had increased odds of feeding their children eggs and fish the previous day.…”
Section: Methodsmentioning
confidence: 72%
“…The 2008 WHO IYCF guidelines for calculating minimum dietary diversity were used for this study because the 2021 WHO IYCF recommendations were not available when the study was designed and conducted. In addition to these indicators, consumption of 2 specific food groups on the previous day (feeding eggs and fish to children aged 6–23 mo), which had been promoted by the intervention ( 25 ), yielded post hoc outcome variables.…”
Section: Methodsmentioning
confidence: 99%
“…In July 2019, Alive & Thrive launched a campaign in Kaduna state promoting complementary feeding, including egg consumption among children (Flax et al, 2022), which could explain the high rates of self-reported exposure to egg promotion messaging in both states at baseline, as the two states are geographically close and the mass media campaign in Kaduna (i.e., television and radio spots) may have reached our study's comparison state of Kano. Similar spillover of mass media messages directed at the intervention state reaching the comparison state could have occurred in our study.…”
Section: Discussionmentioning
confidence: 92%
“…Interventions such as this one may benefit from coupling their ATL and BTL activities with interpersonal communication from, for example, trusted sources of information such as community health workers and religious leaders, to encourage changes in intrahousehold allocation of eggs and the transition from caregiver awareness and self‐efficacy to the practice of feeding eggs to children. In a recent study in Nigeria, complementary feeding social and behaviour change communication targeting both fathers and mothers increased children's consumption of eggs, fish and minimum meal frequency (Flax et al, 2022 ). This type of intervention illustrates the importance of directing messages at fathers and of interpersonal communication through community meetings, religious services and home visits, in addition to mass media, to effectively influence behaviour change.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions were coded on the basis of involving one or more Behaviour Change Wheel intervention functions ( Fig 1 ) [ 28 ]. Functions ( S3 Table ) included education(n = 56) [ 20 , 42 44 , 47 50 , 52 , 54 57 , 58 , 60 , 70 81 , 83 , 84 , 87 , 89 94 , 103 105 , 107 112 , 115 121 ], enablement(n = 56) [ 20 , 42 , 47 50 , 52 , 54 57 , 58 , 61 72 , 75 82 , 85 , 86 , 89 91 , 93 , 94 , 96 , 98 107 , 109 , 113 115 , 117 , 119 121 ], persuasion(n = 46) [ …”
Section: Resultsmentioning
confidence: 99%